2015
DOI: 10.1016/j.jcin.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Causes, and Predictors of Early (≤30 Days) and Late Unplanned Hospital Readmissions After Transcatheter Aortic Valve Replacement

Abstract: The readmission burden after TAVR in an all-comers population was high. Nearly one-fifth of the patients were readmitted early after hospital discharge, increasing the risk of mortality at follow-up. Reasons for readmission were split between noncardiac and cardiac causes, with respiratory causes and heart failure as the main diagnoses in each group, respectively. Whereas early readmissions were mainly related to periprocedural bleeding events, most late readmissions were secondary to baseline patient comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 43 publications
9
81
1
2
Order By: Relevance
“…13 Unplanned readmissions for noncardiac causes greater than for cardiac causes, which is consistent with patients who are at high surgical risk because of various extracardiac comorbidities. 2 Also, TAVI was performed in index admissions and patients were likely to be in a more stable condition from the perspective of cardiovascular disease.…”
Section: Impact Of Frailty Markers In Tavisupporting
confidence: 57%
See 2 more Smart Citations
“…13 Unplanned readmissions for noncardiac causes greater than for cardiac causes, which is consistent with patients who are at high surgical risk because of various extracardiac comorbidities. 2 Also, TAVI was performed in index admissions and patients were likely to be in a more stable condition from the perspective of cardiovascular disease.…”
Section: Impact Of Frailty Markers In Tavisupporting
confidence: 57%
“…13 In our sensitivity analysis, device success and early safety at 30 days did not predict unplanned readmission after TAVI, suggesting most patients in Japan with procedural compli- Advance Publication by-J-STAGE…”
Section: Predictive Factors Of Unplanned Readmissionmentioning
confidence: 78%
See 1 more Smart Citation
“…12 oral anticoagulant, typically warfarin for AF [43,44]. In this setting, the absence of consensus was even more evident and according to the results of this survey, the antithrombotic regimens were highly variable.…”
Section: Accepted M Manuscriptmentioning
confidence: 89%
“…The main causes of noncardiac admission were respiratory diseases, infection, and bleeding. 32 One possible explanation for increased admission in NOP-LBBB patients is that these patients may be more vulnerable to HF exacerbation in the middle of these events (infection and bleeding). However, Urena et al and Testa et al reported no association between NOP-LBBB and HF admission.…”
Section: Permanent Pacemaker Implantation In New-onset Persistent Lefmentioning
confidence: 99%